Ethical Considerations for Healthcare Organizations - Rao, Paul R. (Seminars in Speech and Language, 2020)
Ethical misbehavior in the delivery of healthcare creates harm not only to individual therapists and administrators who might choose to overstep ethical boundaries but also, more broadly, causes harm to patients, to healthcare organizations, to professional organizations, and ultimately to society. Both corporate codes of conduct and professional codes of ethics are important, because they set standards of conduct and penalize noncompliant or unethical conduct. The purposes of this article are (1) to differentiate corporate compliance from ethics in a healthcare organization; (2) to explain the application of ethics principles to organizational and professional behaviors; (3) to discuss three important ethical issues (cultural competence, conflict of interest, and employer demands); and (4) to emphasize that, whether applying a corporate code of conduct or a professional code of ethics (or both), the integrity of each individual is essential to ethical behavior. To illustrate these concepts, ASHA's Code of Ethics is discussed in detail (including the ethics complaint adjudication process), and hypothetical case studies are presented under the macro headings of Cultural Competence, Conflict of Interest, and Employer Demands.
Keywords: compliance; employer demands; conflict of interest; cultural competence; fraud and abuse